The complete larval development of Pagurus maculosus Komai & Imafuku, 1996 (Decapoda, Anomura, Paguridae) reared in the laboratory, and a comparison with sympatric species - Sultana, Zakea; Asakura, Akira (Zootaxa, 2015)
The complete larval development of the hermit crab Pagurus maculosus, is described and illustrated based on specimens reared in the laboratory at 15°C and 33–35 PSU. Newly hatched larvae invariably passed through a short prezoeal stage (10 minutes to 2 hours), four zoeal stages (each of 7 days,) and one megalopal stage (14 days). Distinct morphological features of each larval stage of the present study are compared with other closely related species in Japanese waters, and we found many differences in morphology and the duration of zoeal stages between them. We mentioned significant diagnostic characters separating this species from other congeners in Japanese waters that include the presence of red-yellowish chromatophores on the maxillipeds. This is the first report of complete larvae development of Pagurus maculosus.